Thorstein Veblen: A marxist starting point - Kirsten Ford; William McColloch (The University of Utah, Department of Economics, 2011)
As existing literature attests, in spite of methodological differences Marx and Veblen draw strikingly similar conclusions regarding production, conflict, and alienation in modern existence. We here attempt to establish that similarity in conclusion stems from similarity in approach. After reviewing the existing literature on a Marx-Veblen methodological reconciliation, we recapitulate Marx's method, making the mediated starting point the locus of discussion. From this vantage point, we then examine Veblen's own approach to analysis in The Theory of Business Enterprise and the conclusions that emerge as they resemble those of Marx. In taking a kindred approach Veblen is able to arrive at an understanding of capitalism in accordance with, and complementary to, Marx's rendering of the inverted nature of economic life in modernity.
Keywords: B14; B15; B30; B40; 330; Marxism; Institutionalism; History of Economic Thought: Individuals; Economic Methodology: General